Artificial intelligence systems in cyber security and their capabilitiesfront modern cyber threats - Даков, Сергій; Маньковський, Д.; Білоконь, І. (Київський національний університет імені Тараса Шевченка, 2025)
B a c k g r o u n d . In recent years, the level of cybercrime has grown rapidly. The complexity and diversity of these threats has forced organizations to prioritize advanced cybersecurity solutions, including the use of artificial intelligence technologies that can quickly analyze data to identify potential threats and anomalies. By 2027, the AI-based cybersecurity market is expected to exceed $46 billion. However, as AI strengthens and refines defenses, cybercriminals are adapting by exploiting vulnerabilities and even using AI to enhance attacks. This dual use of AI underscores the need for balanced and intelligent strategies that combine the predictable capabilities of AI with human knowledge and talent. M e t h o d s . My Research highlights effective risk prevention strategies, including promoting a security-aware culture, implementing strong passwords and two-factor authentication, regularly assessing and updating systems, enhancing firewalls, and adhering to cybersecurity regulations. AI proves valuable in threat detection and response, giving companies a competitive edge, though it raises concerns about reducing human roles in security tasks. R e s u l t s . The research indicates that AI positively impacts cybersecurity by enabling faster detection and response to threats, allowing organizations to proactively identify and address vulnerabilities. Companies that integrate AI into their cybersecurity strategies gain an advantage in managing complex cyber threats. However, concerns persist about AI's dual-use nature, as it could also be leveraged by cybercriminals for advanced attacks. This potential for AI to operate independently raises questions about the diminishing role of human oversight. Ultimately, the findings stress the need for a balanced approach: while AI is essential for modern cybersecurity, human involvement remains crucial. Continuous adaptation and a blend of technological and human expertise are necessary to protect critical infrastructure and data. C o n c l u s i o n s . To summarise, the rapid growth of cybercrime underscores the necessity for robust cybersecurity measures to protect sensitive information and ensure operational integrity. Artificial Intelligence is becoming crucial in enhancing cybersecurity through advanced threat detection, pattern recognition, and predictive analysis. While AI offers significant benefits, it can also be exploited by cybercriminals, highlighting the importance of vigilance and innovation in security strategies. Despite advancements in AI, human expertise remains vital for interpreting insights, making informed decisions, and adapting to new threats. A multi-faceted approach, including employee training, regular audits, and strong data protection, is essential for effective cybersecurity. Enhanced cooperation among organizations, governments, and international partners is crucial for developing effective strategies to combat cybercrime. Continued research into AI capabilities and ethical considerations is necessary to address the evolving landscape of cybersecurity threats.

В с т у п . Останніми роками рівень кіберзлочинності стрімко зріс. Складність і різноманітність цих загроз змусили організації віддавати пріоритет передовим рішенням із кібербезпеки, включаючи використання технологій штучного інтелекту, які можуть швидко аналізувати дані для виявлення потенційних загроз і аномалій. Очікують, що до 2027 р. ринок кібербезпеки на основі ШІ перевищить 46 млрд дол. Однак, оскільки штучний інтелект зміцнює та покращує захист, кіберзлочинці адаптуються, використовуючи вразливості та навіть застосовуючи штучний інтелект для посилення атак. Таке подвійне використання ШІ підкреслює необхідність збалансованих і розумних стратегій, які поєднують передбачувані можливості ШІ з людськими знаннями та талантом. М е т о д и . Наведене дослідження зазначає ефективні стратегії запобігання ризикам, зокрема і сприяння культурі безпеки, впровадження надійних паролів і двофакторної автентифікації, регулярне оцінювання й оновлення систем, удосконалення брандмауерів і дотримання правил кібербезпеки. Штучний інтелект доводить свою цінність у виявленні загроз і реагуванні на них, надаючи компаніям конкурентну перевагу, хоча викликає занепокоєння зменшення ролі людини в задачах безпеки. Р е з у л ь т а т и . Дослідження показує, що штучний інтелект позитивно впливає на кібербезпеку, забезпечуючи швидке виявлення загроз і реагування на них, дозволяючи організаціям завчасно виявляти й усувати вразливості. Компанії, які інтегрують штучний інтелект у свої стратегії кібербезпеки, отримують перевагу в керуванні складними кіберзагрозами. Проте все ще викликає занепокоєння подвійне використання штучного інтелекту, оскільки його також можуть використовувати кіберзлочинці для розширених атак. Потенціал штучного інтелекту працювати незалежно ставить питання про зменшення ролі людського нагляду. Зрештою, результати підкреслюють необхідність збалансованого підходу: хоча ШІ є важливим для розв'язання задач сучасної кібербезпеки, участь людини у цьому процесі залишається вирішальною. Для захисту критичної інфраструктури та даних необхідні постійна адаптація і поєднання технологічного та людського досвіду. В и с н о в к и . Швидке зростання кіберзлочинності свідчить про необхідність розроблення надійних заходів кібербезпеки для захисту конфіденційної інформації та забезпечення операційної цілісності. Штучний інтелект стає вирішальним у підвищенні кібербезпеки за допомогою розширеного виявлення загроз, розпізнавання образів і прогнозного аналізу. Хоча штучний інтелект пропонує значні переваги, ним також можуть скористатися кіберзлочинці, що підкреслює важливість пильності й інновацій у стратегіях безпеки. Незважаючи на прогрес ШІ, людські знання залишаються життєво важливими для інтерпретації інформації, прийняття обґрунтованих рішень і адаптації до нових загроз. Для ефективної кібербезпеки важливий багатогранний підхід, включаючи навчання співробітників, регулярні аудити та надійний захист даних. Розширена співпраця між організаціями, урядами та міжнародними партнерами має вирішальне значення для розроблення ефективних стратегій боротьби з кіберзлочинністю. Необхідно продовжувати дослідження можливостей штучного інтелекту й етичних міркувань, щоб подолати мінливий ландшафт загроз кібербезпеці.
Системи штучного інтелекту в кібербезпеці та їхні можливості протистояти сучасним кіберзагрозам
Keywords: artificial intelligence; measures; strategy; cybersecurity; threats; analysis; штучний інтелект; заходи; стратегія; кібербезпека; загрози; аналіз